Optimization of ATC Radar Simulator Utilization for Personnel Rating at Jakarta Air Traffic Service Centre - Rizky Arlanda Sihombing; Nunuk Praptiningsih; Yudha Abimanyu (CV. AFDIFAL MAJU BERKAH, 2026)
Aviation safety largely depends on the competence of Air Traffic Controllers (ATCs). The Jakarta Air Traffic Service Centre (JATSC), managing the Jakarta Flight Information Region (FIR), faces increasing operational complexity following the Jakarta–Singapore FIR realignment. This study aims to analyze the utilization of the ATC radar simulator in JATSC’s training programs and its impact on improving ATC personnel competence. A descriptive-correlational quantitative method was applied, involving 81 ATC personnel selected through purposive sampling. Data were collected via structured questionnaires and analyzed using SPSS with validity, reliability, and correlation tests. The overall simulator utilization was categorized as high (mean = 3.87), with excellent feature quality (mean = 4.15) and strong operational relevance (mean = 3.99), though usage intensity remained moderate (mean = 2.97) due to scheduling constraints. The simulator effectively enhanced ATC competence (mean = 4.42), particularly in decision-making, workload management, situational awareness, and teamwork, while communication required improvement. Correlation results indicated that simulator feature quality had the strongest relationship with competency dimensions (r = 0.532–0.687). The study concludes that optimal simulator utilization significantly improves ATC competence, providing a strategic model for enhancing aviation training and safety.